Evidence on the long shadow of poor mental health across three generations - David W. Johnston; Stefanie Schurer; Michael A. Shields (Institute for the Study of Labor (IZA), 2011)
Individuals suffering from mental health problems are often severely limited in their social and economic functioning. Mental health problems can develop early in life, are frequently chronic in nature, and have an established hereditary component. The extent to which mental illness runs in families could therefore help explain the widely discussed intergenerational transmission of socioeconomic disadvantage. Using data from three generations contained in the 1970 British Cohort Study, we estimate the intergenerational correlation of mental health between mothers, their children, and their grandchildren. We find that the intergenerational correlation in mental health is about 0.2, and that the probability of feeling depressed is 63 percent higher for children whose mothers reported the same symptom 20 years earlier. Moreover, grandmother and grandchild mental health are strongly correlated, but this relationship appears to work fully through the mental health of the parent. Using grandmother mental health as an instrument for maternal mental health in a model of grandchild mental health confirms the strong intergenerational correlation. We also find that maternal and own mental health are strong predictors of adulthood socioeconomic outcomes. Even after controlling for parental socioeconomic status, own educational attainment, and own mental health (captured in childhood and adulthood), our results suggest that a one standard deviation reduction in maternal mental health reduces household income for their adult offspring by around 2 percent.
urn:nbn:de:101:1-201110263526
Keywords: I12; I14; J62; 330; intergenerational transmission; mobility; mental health; economic outcomes; Psychische Störung; Generationenbeziehungen; Sozialer Status; Soziale Mobilität; Großbritannien